A rapid and simple pipeline for synthesis of mRNA–ribosome–VHH complexes used in single-domain antibody ribosome display1. Issue 6 (19th June 2015) - Bencurova, Elena; Pulzova, Lucia; Flachbartova, Zuzana; Bhide, Mangesh
<x xml:space="preserve">Abstract</x> A simple and rapid technique for construction of single domain antibody (VHH) library for ribosome display is described in this study.